Pemanfaatan dinding sebagai permukaan kondensasi untuk meningkatkan kinerja solar still double slope - Nova Risdiyanto Ismail; Purbo Suwandono; Dadang Hermawan; Frida Dwi Anggraeni (TURBO [Tulisan Riset Berbasis Online], 2023)
Indonesia is an archipelagic country that often experiences drought, especially in the dry season. In the dry season, there is very abundant solar and seawater energy, so to overcome the problem, you can use solar still technology that utilizes solar energy to process seawater into condensate / fresh water economically. Various efforts are made to optimize the performance of solar stills, in this case the study aims to utilize the wall as a condensation surface to improve the performance of solar still double slope. The study was conducted experimentally by comparing: 1. Solar still double slope without utilizing the wall as a condensing surface, 2. Solar still double slope by utilizing the north side wall as a condensing surface, 3. Solar still double slope by utilizing the south side wall as a condensation surface, and 4. Solar still double slope by utilizing the north and south side walls as condensing surfaces. The results of the study using solar still double slope by utilizing the north wall as a condensing surface obtained the highest productivity of 1966 ml and the highest efficiency of 68.58%.